PENGARUH FREKUENSI PEMBERIAN PAKAN KOMERSIAL TERHADAP PERTUMBUHAN BERAT MUTLAK UDANG VANAME (Litopenaeus vannamei) UMUR PL 8-21 DI CV. ZELDA SUMENEP KABUPATEN SUMENEP - Fabian Rahmando Ahmed; Muhajir Muhajir; Achmad Kusyairi (Jurnal Perikanan Unram, 2024)
One important factor in feeding management is the frequency of feeding, namely the number of times feed is given in one day. If this feeding frequency is used incorrectly, it can certainly affect the growth and survival of the shrimp. This study aims to determine the optimal commercial feeding frequency for the absolute weight growth vannamei shrimp (Litopennaeus vannamei) PL ages 8-21 at CV. Zelda Sumenep, Sumenep District. This study used an experimental method with a completely randomized design (CRD) with 4 treatments with 6 replications. The treatment in this study was the frequency of commercial feeding, treatment A; frequency of commercial feeding 2 times/day, treatment B ; frequency of commercial feeding 3 times/day, treatment C ; frequency of commercial feeding 4 times/day, and treatment D ; frequency of commercial feeding 5 times/day. The test animals used in this study were vannamei shrimp PL ages 8-21 with an average weight of 0,001 g/head. The stocking density was 1 head/liter and the experimental medium used fresh water with a volume of 15 liters/tub. The results showed that treatment D gave the highest results for the absolute weight growth of vannamei shrimp (Litopenaeus vannamei) PL 8-21 of 0,053 g. Water quality data obtained water temperatures ranged from 27,3 oC – 27,5 oC, acidity ranged from 7,7 – 7,72 and dissolved oxygen ranged from 6,17 – 6,21 ppm.